Influence of hydrogen on a nanocrystalline high-entropy oxide with application potential in hydrogen technologies. Issue 10 (15th May 2023) - Domaradzki, Kamil; Nowak, Marek; Sitarz, Maciej; Łapiński, Marcin; Brylewski, Tomasz; Jurczyk, Mieczysław
Abstract: The influence of hydrogen on a (Co0·2 Cu0·2 Mg0·2 Ni0·2 Zn0.2 )O HEO with a rock salt structure was studied. Two forms of this HEO (nanopowder and sinter) were prepared via mechanochemical synthesis (MS) and additional heat treatment, respectively. The chemical stability of the synthesized samples in a pure hydrogen atmosphere was investigated using Sievert's technique. High-pressure hydrogenation at 250 °C had no noticeable effect on the HEO sinter. The sintered sample was chemically, structurally, and morphologically stable, as confirmed via the XRD, Raman spectroscopy, SEM, and XPS techniques. Thermogravimetric analysis (TGA) showed the sinter to be stable in an argon gas mixture with 5 vol% of hydrogen and over the temperature range of up to 400 °C. Highlights: Mechanochemical synthesis (MS) is effective at synthesizing HEO nanopowder in Ar. Two types of (Co0·2 Cu0·2 Mg0·2 Ni0·2 Zn0.2 )O samples were prepared. PCT tests did not affect the structure and microstructure of sintered HEO. Sintered HEO with a rock salt structure is stable in hydrogen media up to 400 °C.